Crowd-sourced investigation of a potential relationship between Bartonella-associated cutaneous lesions and neuropsychiatric symptoms - Stewart, Zachary; Korsapathy, Sanvi; Frohlich, Flavio (Frontiers in Psychiatry, 2023)
Preliminary studies suggest that infection with BartonellaBartonella bacteria can not only cause a characteristic rash, headache, fever and fatigue, but also neuropsychiatric symptoms. To date, this association has only been reported in case studies and it remains unclear if this association generalizes to larger samples. We used Amazon's Mechanical Turk (MTurk) to crowdsource a large sample (N=996) of individuals to ascertain the extent to which the presence of participant-identified bartonellaBartonellaassociated cutaneous lesions (BACL) were associated with self-report measures of anxiety, depression, and schizotypy. Participants were asked to select images of cutaneous lesions they had seen on their own body and complete a battery of self-report questionnaires to assess psychiatric symptoms. Participants were not informed that the focus of the study was on potential dermatological lesions associated with BartonellaBartonella. Point-biserial correlations were used to determine the potential relationship between selecting a BACL image and severity of self-reported psychiatric symptoms. Scores of anxiety, depression and schizotypy were positively and significantly correlated with selecting a BACL image. Furthermore, self-report scores of 10 or higher on the GAD-7 and PHQ-9, which represent the suggested clinical cutoffs for meeting criteria for a depressive or anxiety-related disorder, were also significantly associated with selecting a BACL image. Non-BartonellaBartonella-associated cutaneous legions were also significantly associated with self-report measures of psychiatric symptoms. Further investigation is recommended to expand on these findings.